Impact of Racial/Ethnic Discrimination on Quality of Life Among Breast Cancer Survivors: The Pathways Study. Issue 3 (1st December 2022) - Shariff-Marco, Salma; Sangaramoorthy, Meera; Ellis, Libby; Thomsen, Catherine; Roh, Janise M; Kroenke, Candyce; Valice, Emily; Kwan, Marilyn L; Ambrosone, Christine; Kushi, Lawrence; Gomez, Scarlett Lin
Abstract: Although racial/ethnic disparities in health-care access, treatment, and cancer outcomes are well documented, the impact of racial/ethnic discrimination on cancer survivorship is unclear. We examined associations between quality of life (QoL) and self-reported discrimination among 3, 991 women with breast cancer recruited during 2006–2013 from the Pathways Study in the Kaiser Permanente Northern California integrated health-care system, using linear regression models. Overall, 31% of women reported experiencing racial/ethnic discrimination, with differences by race/ethnicity (82% among non-Hispanic Black women vs. 19% among non-Hispanic White women) and nativity (40% among foreign-born Hispanic women vs. 76% among US-born Asian-American women). Experiencing racial/ethnic discrimination was associated with lower QoL in fully adjusted models. The mean QoL score was 119.6 (95% confidence interval (CI): 102.0, 137.1) for women who did not report discrimination, 115.5 (95% CI: 98.0, 133.0) for those who reported some discrimination/less than the median level, and 110.2 (95% CI: 92.7, 127.7) for those who reported more discrimination/greater than or equal to the median level. Discrimination was associated with lower QoL among women who used passive coping strategies or lived in neighborhoods with high neighborhood socioeconomic status, neighborhoods with high levels of segregation, or non–ethnic enclaves. Among breast cancer survivors, clinically meaningful differences in QoL scores were associated with racial/ethnic discrimination. Additional studies are needed to understand potential pathways through which these social factors affect survivorship outcomes.